Korelasi Antara Gaya Belajar Dengan Hasil Belajar Pendidikan Agama Islam Pada Siswa Kelas VII SMPN 4 Kecamatan Pangkalan Koto Baru - Desfi Maiza; Supriadi Supriadi; Wedra Aprison; Januar Januar (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
Learning style is an important aspect that must be considered in the learning process. This research was motivated by the discovery of problems where there were several students who had difficulty adapting their way of learning to the teacher's way of teaching in class, students did not understand the subject matter, and many students' learning outcomes were below the standard of completeness. The purpose of the study was to determine whether there was a correlation between learning styles and Islamic Religious Education learning outcomes for class VII students at SMPN 4 Pangkalan Koto Baru District for the 2022/2023 academic year. This type of correlational research uses a quantitative approach. The research sample of all class VII students was 44 people. Research data collection techniques use questionnaires and tests. Data analysis uses the r person product moment test. According to the data analysis, the sig value was obtained. (2-tailed) learning styles and learning outcomes 0.000 < 0.05 at a significance level of 5%, the value obtained is rcount = 0.711 > rtable = 0.304, meaning that the Ha hypothesis is accepted that there is a positive significant correlation between learning styles and Islamic Religious Education learning outcomes for class students VII at SMPN 4 Pangkalan Koto Baru District for the 2022/2023 academic year and Ho was rejected. The correlation coefficient value obtained is 0.711, meaning there is a strong correlation. The coefficient of determination obtained is 0.506 so it can be interpreted that learning style has a moderate contribution of 50.6% and the rest is influenced by other factors..